2009
DOI: 10.1097/ta.0b013e318190c3d3
|View full text |Cite
|
Sign up to set email alerts
|

Surveyed Opinion of American Trauma, Orthopedic, and Thoracic Surgeons On Rib and Sternal Fracture Repair

Abstract: A majority of surveyed surgeons reported that rib and sternal fracture repair is indicated in selected patients; however, a much smaller proportion indicated that they had performed the procedures. The published literature on surgical repair is sparse and unfamiliar to most surgeons. Barriers to surgical repair of rib and sternal fracture include a lack of expertise among TRS, lack of research of optimal techniques, and a dearth of randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 35 publications
1
87
0
5
Order By: Relevance
“…The results in the current study were similar to these studies. Long-term disability is reported in over one third of these patients [21]. In our study, return to full-time employment was found to be 85.71 % in the surgical group, whereas it was only 47.06 % in the non-surgical group.…”
Section: Discussionmentioning
confidence: 51%
“…The results in the current study were similar to these studies. Long-term disability is reported in over one third of these patients [21]. In our study, return to full-time employment was found to be 85.71 % in the surgical group, whereas it was only 47.06 % in the non-surgical group.…”
Section: Discussionmentioning
confidence: 51%
“…Our results are also supported by a recent survey where the majority of surveyed surgeons reported that rib and sternal fracture repair is indicated in selected patients; even if a much smaller proportion indicated that they had performed the procedures. 13 We conclude that surgical stabilization of severe flail chest with titanium clips has been a safe and effective treatment option in selected patients in our series. The primary rational for fixation of rib fractures is to reduce early respiratory morbidity due to chest wall deformities.…”
Section: Discussionmentioning
confidence: 88%
“…That is why in 2009 Mayberry et al discussed the issue of different surgical disciplines involved in the performance of chest surgery. There lies the reluctance of various surgical, and in particular, orthopaedic disciplines, to make any fixation of the chest [13]. Another aspect of the implants is sometimes their poor patient acceptance and/or soft tissue irritation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mayberry et al discussed this issue in 2009 in association with the competency of the various surgical disciplines [13]. An orthopedic surgeon would have a high confidence in dealing with plate fixation, however, would be reluctant to operate on the chest.…”
Section: Introductionmentioning
confidence: 99%